CRYPTOCURRENCY MARKET DYNAMICS AROUND BITCOIN FUTURES EXPIRATION EVENTS - Vojtko, Radovan; Dujava, Cyril (The journal of contemporary issues in business and government, 2024)
In the rapidly evolving landscape of cryptocurrency markets, understanding the underlying dynamics that drive price movements and investor sentiment can be a matter of survival. However, there are myriad facets of trading reality, and the only thing that we can do is to slowly understand them one after another, one step at a time. This article picks one corner of the cryptocurrency market and sheds a little light on it. We have already written a few times about the importance of the introduction of Bitcoin futures and their impact on the Bitcoin price. Therefore, in this article, we will specifically examine Bitcoin’s behavior around the critical events when Bitcoin futures expire.